Targeted Approach to Ligation of Feeding Vessels Based on Preoperative Imaging in Resection of Juvenile Nasopharyngeal Angiofibroma Obviating Preoperative Embolization - Janakiram Trichy Narayanan; Mansi A R Venkatramanan; Soumya Sampath; Arun Kumar G; Bavaharan Rajalingam (European Journal of Rhinology and Allergy)
Objective: Juvenile Nasopharyngeal Angiofbroma (JNA) is a benign, yet locally aggressive tumor with a rich blood supply. Surgical management is the mainstay treatment for JNA, however, blood loss is a big concern during surgery. This retrospective study aims to evaluate the efcacy of ligating the feeding vessels of JNA based on preoperative imaging, potentially eliminating the need for preoperative embolization.